2009
DOI: 10.1371/journal.pone.0006589
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Expression Profiling and ChIP-seq Analyses of the Growth Inhibition Response Program of the Androgen Receptor

Abstract: BackgroundThe androgen receptor (AR) plays important roles in the development of male phenotype and in different human diseases including prostate cancers. The AR can act either as a promoter or a tumor suppressor depending on cell types. The AR proliferative response program has been well studied, but its prohibitive response program has not yet been thoroughly studied.Methodology/Principal FindingsPrevious studies found that PC3 cells expressing the wild-type AR inhibit growth and suppress invasion. We appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
73
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(75 citation statements)
references
References 45 publications
1
73
0
1
Order By: Relevance
“…For example Niu et al (25) noted that restoring AR in PC3 cells could suppress their ability to invade in vitro and in vivo. whereas Lin et al (26) hypothesize that PC3 cells possess cellular machinery that turns the AR in PC3-AR cells into a growth suppressor. In another study, an equally interesting observation is that RLN2 is negatively regulated by androgens in prostate cancer (in vitro and in vivo) through the AR, implying that RLN2 levels increase in the both the absence of androgens and their ablation (27).…”
Section: Discussionmentioning
confidence: 99%
“…For example Niu et al (25) noted that restoring AR in PC3 cells could suppress their ability to invade in vitro and in vivo. whereas Lin et al (26) hypothesize that PC3 cells possess cellular machinery that turns the AR in PC3-AR cells into a growth suppressor. In another study, an equally interesting observation is that RLN2 is negatively regulated by androgens in prostate cancer (in vitro and in vivo) through the AR, implying that RLN2 levels increase in the both the absence of androgens and their ablation (27).…”
Section: Discussionmentioning
confidence: 99%
“…Expression of AR in the AR-null prostate cancer cell line PC3 under different doses of androgen stimulation has been shown to result in differential gene expression, with approximately 5.7% of these genes involved in cell survival/apoptosis pathways (43). Such phenotypic effects observed upon androgen signaling generally occur through regulation of critical cell survival pathways, such as the insulin-like growth factor 1 (IGF-1), epidermal growth factor (EGF), and mitogen-activated protein kinase (MAPK) signaling pathways, as well as cell death pathways, such as the transforming growth factor ␤1 (TGF-␤1), p53, or death receptor-mediated, caspase-dependent apoptotic pathway (21,77).…”
mentioning
confidence: 99%
“…Recently by combining chromatin immunoprecipitation with tiled oligonucleotide microarrays (ChIP-on-chip) or with massively parallel sequencing (ChIP-Seq), the genome-wide AR binding sites (termed "AR cistrome") have been identified from a variety of PCa cell lines in multiple independent studies [46][47][48][49][50]. It was found that contrary to our expectation, most of the experimentally defined AR binding sites contain noncanonical AREs that are shown to be functional.…”
Section: Ar Signaling: New Advances In the Mechanistic Studymentioning
confidence: 77%
“…Another noteworthy discovery is that co-occupancy of AR with other transcription factors, such as FOXA1, TEF1, PU1, GATA2 and OCT1 [46,49], was frequently found in AR-binding sites, suggesting that AR may be working in collaboration with other transcription factors to control the expression of androgen-responsive genes. In support of this view, FOXA1, the DNA-binding transcription factor that contains chromatin-remodeling activity, has been found to serve as a pioneer factor binding to the FKH motif that is often concurrent with the AREs (> 60% concurrent rate in PCa cells at the basal state [51]), opening the compacted chromatin, and allowing subsequent association of AR at the AREs within these enhancers to cooperatively regulate target gene expression.…”
Section: Ar Signaling: New Advances In the Mechanistic Studymentioning
confidence: 99%